(untitled) (Clinics, 2022)
Objectives: This study aims to explore the effect of silencing Beclin-1 gene on autophagy and apoptosis of Benign Prostatic Hyperplasia (BPH) (BPH-1) cells under the condition of Androgen Deprivation (AD) and Autophagy Inhibition (AI). Methods: Control group (BPH-1 group), empty carrier group (sh-RNA-BPH-1 group) and Beclin-1 silenced group (sh-Beclin1-BPH-1 group) were set. The Beclin-1 gene silencing efficiency was detected by RT-PCR and Western blot. Autophagic flux was monitored by GFP-LC3 cleavage assay and cell apoptosis was analyzed by flow cytometry. The protein expression levels of LC3, Caspase-3, PARP-1, Bcl-2, and Bax were detected by Western blot. Results: The transfection of sh-Beclin-1 obviously down-regulated the expression of Beclin-1 at both mRNA and protein levels. Under the conditions of AD and AI, silencing of Beclin-1 restrained the autophagy of BPH-1 cells, as evidenced by a decreased number of autophagosomes and down-regulation of LC3-II protein (p < 0.001). The results of flow cytometry showed that the apoptotic rate of sh-Beclin-1 group was elevated significantly compared to the other two groups (p < 0.01). Western blot results showed that silencing of Beclin-1 promoted 89 kd fragmentation of PARP-1 (p < 0.001) and Caspase-3 activation (p < 0.01). Moreover, silencing of Beclin-1 resulted in declined Bcl-2 and augmented Bax protein expression in BPH-1 cells (p < 0.01), which ultimately led to a decreased Bcl-2/Bax ratio. Conclusions: The results indicated that the silencing of Beclin-1 gene hampered autophagy while activating apoptosis in BPH-1 cells. Thus, Beclin-1 may participate in an antagonistic relationship between autophagy and apoptosis in BPH.